Increased BCAR1 predicts poor outcomes of non-small cell lung cancer in multiple-center patients - Deng, Bo (2013)
OBJECTIVE: We aimed to study the prognostic value of BCAR1 expression and its associations with clinical-demographical characteristics in multiple centers of non-small cell lung cancer (NSCLC) patients. METHODS: Gene expression microarray (mRNA) of 77 adenocarcinomas from Mayo Clinic, RNA-sequencing of 508 NSCLC from The Cancer Genome Atlas (TCGA), and immunohistochemistry(IHC) stain of BCAR1-protein expression in 150 cases from Daping Hospital were included in the study. The association of mRNA or protein expression with patient clinical characteristics and overall survival was assessed in each dataset. We also predicted microRNAs (miRNA) that target BCAR1- using bioinformatics prediction tools and evaluated miRNA expression patterns with BCAR1 expression in miRNA-sequencing data of 74 lung cancer cases from TCGA dataset. RESULTS: In the Mayo Clinic dataset, a higher BCAR1-mRNA level was significantly correlated with more advanced tumor-stage and lymphatic metastasis. Similar changes were observed in the TCGA RNA-seq dataset. Additionally, higher BCAR1-mRNA levels predicted poorer survival in adenocarcinoma and squamous carcinoma from the TCGA dataset. The protein levels in the adenocarcinoma cases with lymphatic metastasis were significantly higher than of those without metastasis. Tumor tissues demonstrated remarkably higher levels of protein compared with matched normal tissues although there was no significant difference in BCAR1-mRNA expression between tumor and matched normal tissues was detected. In miRNAs that were down-regulated in the tumors, Let-7f-2 and miR-22 differed the most (P<0.001 and P=0.007, respectively). CONCLUSION: We confirmed that increased BCAR1 expression predicts poorer prognosis in NSCLC. We postulate mRNA-protein decoupling of BCAR1 may be a result of reduced inhibition of specific miRNAs in tumor tissues, which warrants further study.